Mobile payments: a scoping study of the literature and issues for future research: - Albuquerque, João Porto de; Diniz de Figueiredo, Eduardo H.; Kemmer Cernev, Adrian (Information development, 2016)
Despite its huge potential, the use of mobile technology for carrying out payment transactions and replicating monetary features, has only taken off in a limite...
First Published December 1, 2014
Gesehen am 06.05.2020